Τ cell-mediated adaptive immunity in the transition from metabolic dysfunction-associated steatohepatitis to hepatocellular carcinoma - Papadopoulos, Grigorios; Giannousi, Eirini; Avdi, Aikaterini P.; Velliou, Rallia-Iliana; Nikolakopoulou, Polyxeni; Chatzigeorgiou, Antonios (Frontiers in Cell and Developmental Biology, 2024)
Metabolic dysfunction-associated steatohepatitis (MASH) is the progressed version of metabolic dysfunction-associated steatotic liver disease (MASLD) characterized by inflammation and fibrosis, but also a pathophysiological “hub” that favors the emergence of liver malignancies. Current research efforts aim to identify risk factors, discover disease biomarkers, and aid patient stratification in the context of MASH-induced hepatocellular carcinoma (HCC), the most prevalent cancer among MASLD patients. To investigate the tumorigenic transition in MASH-induced HCC, researchers predominantly exploit preclinical animal-based MASH models and studies based on archived human biopsies and clinical trials. Recapitulating the immune response during tumor development and progression is vital to obtain mechanistic insights into MASH-induced HCC. Notably, the advanced complexity behind MASLD and MASH pathogenesis shifted the research focus towards innate immunity, a fundamental element of the hepatic immune niche that is usually altered robustly in the course of liver disease. During the last few years, however, there has been an increasing interest for deciphering the role of adaptive immunity in MASH-induced HCC, particularly regarding the functions of the various T cell populations. To effectively understand the specific role of T cells in MASH-induced HCC development, scientists should urgently fill the current knowledge gaps in this field. Pinpointing the metabolic signature, sketching the immune landscape, and characterizing the cellular interactions and dynamics of the specific T cells within the MASH-HCC liver are essential to unravel the mechanisms that adaptive immunity exploits to enable the emergence and progression of this cancer. To this end, our review aims to summarize the current state of research regarding the T cell functions linked to MASH-induced HCC.